KARAKTERISTIK MUTU BAKSO BELUT (Monopterus albus) DENGAN VARIASI SUBSTITUSI TEMPE - Lina Widawati; Novian Firnando; Meirita Sari; Darius Darius (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Meatballs are a type of processed food made from chopped fresh meat, fillers, binders and spices. Besides beef, meatballs can also be made from eel meat because eel meat has a high enough protein. Tempe can be used as a substitute for eel meat because the price of tempe is more affordable and the protein content is also quite high. The purpose of this study was to analyze the effect of the composition of eel and tempe on the protein and organoleptic content of eel meatballs. The results of the analysis showed that the more use of tempe composition, the meatball protein content increased by 19.27%. The results of organoleptic analysis of the color, taste, aroma and texture of meatballs with the treatment of eel and tempe composition showed significant differences. The more the use of tempe composition the assessment of color, taste, flavour and texture is decrease. The results of the average color oranoleptic are between 3,75 (likes) to 4,25 (likes), the average organoleptic taste is between 3,65 (likes) to 4,05 (likes), the average organoleptic flavour is between 3,35 (rather likes) to 4,30 (likes) and organoleptic texture averages between 3,65 (likes) to 4,20 (likes). Kata Kunci : meatballs; eel meat; tempe